2023
DOI: 10.3390/molecules28020509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3d Transition Metal Atom Intercalation Concentration on the Electronic and Magnetic Properties of Graphene/MoS2 Heterostructure: A First-Principles Study

Abstract: The electronic and magnetic properties of graphene/MoS2 heterostructures intercalated with 3d transition metal (TM) atoms at different concentrations have been systematically investigated by first principles calculations. The results showed that all the studied systems are thermodynamically stable with large binding energies of about 3.72 eV–6.86 eV. Interestingly, all the TM-intercalated graphene/MoS2 heterostructures are ferromagnetic and their total magnetic moments increase with TM concentration. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…To date, many effective strategies, such as doping/adsorbing magnetic atoms or molecules, creating atomic defects, and so on [20][21][22][23][24][25] have been proposed for the magnetic manipulation of 2D materials, however, most of them suffer from the lattice deformation or the clustering of metal atoms, and so forth. Alternatively, intercalation technique, by intercalating atoms or molecules into van der Waals (vdW) layered materials, has the advantage of adjusting the electronic structure of the host's internal region without destroying the single-layer structure [26][27][28][29][30]. For example, Zhao et al [31] found that intercalating Ta into bilayer TaS 2 can introduce intercalation concentration dependent electronic properties, and the magnetic properties of 2D Ta x S y can be manipulated by the intercalation amount, dimensionality, and structural homogeneity.…”
mentioning
confidence: 99%
“…To date, many effective strategies, such as doping/adsorbing magnetic atoms or molecules, creating atomic defects, and so on [20][21][22][23][24][25] have been proposed for the magnetic manipulation of 2D materials, however, most of them suffer from the lattice deformation or the clustering of metal atoms, and so forth. Alternatively, intercalation technique, by intercalating atoms or molecules into van der Waals (vdW) layered materials, has the advantage of adjusting the electronic structure of the host's internal region without destroying the single-layer structure [26][27][28][29][30]. For example, Zhao et al [31] found that intercalating Ta into bilayer TaS 2 can introduce intercalation concentration dependent electronic properties, and the magnetic properties of 2D Ta x S y can be manipulated by the intercalation amount, dimensionality, and structural homogeneity.…”
mentioning
confidence: 99%